A new barusuchid (Crocodyliformes Notosuchia) from the Adamantina Formation (Bauru Group, Late Cretaceous), and a new phylogenetic analysis of notosuchians - Martins, Kawan Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Os Baurusuchidae compõem um grupo de notossuquios do Cretáceo Superior da América do Sul. São caracterizados por possuírem rostro curto e alto, número de dentes reduzidos e ziphodontes, e caninos hipertrofiados. Nesse estudo, nós descremos um novo baurusuquídeo da Formação Adamantina (Grupo Bauru), no sudeste brasileiro. O novo táxon consiste de um fragmento da porção direita de um crânio, e elementos do teto craniano, fragmentos do palato secundário e do maxilar inferior, assim como, seis dentes desarticulados. O novo espécime corresponde ao Gênero Aphaurosuchus, devido a presença de uma depressão posterior do nasal e a crista infraorbital do jugal voltada para cima. A espécie Aphaurosuchus kaiju foi determinada com base em caracteres que a distinguem do Aphaurosuchus escharafacieis, assim como uma profunda depressão do frontal, uma depressão longitudinal na linha media do frontal, presença de uma crista contida na depressão do frontal, e um parietal sem projeção posterior sobre a fenestra supratemporal. Para entender a posição filogenética do Aphaurosuchus kaiju entre os baurusuquídeos, bem como as afinidades taxonômicas de supostos baurusuquia recém descritos e revisados, realizamos uma análise filogenética atualizada que combinou as informações sobre os Baurusuchia das três matrizes mais atualizadas e independentes disponíveis. Recuperamos as duas principais linhagens de Baurusuchidae, Pissarrachampsinae e Baurusuchinae conforme proposto originalmente. Adicionalmente, recuperamos Ogresuchus furatus e Razanandrongobe sakalavae como baurusuquia não baurusuquídeos. A nova posição filogenética para esses dois táxons aumenta a distribuição espacial e o alcance temporal de Baurusuchia

Baurusuchidae is a group of notosuchian crocodyliforms ubiquitous in the Late Cretaceous deposits in South America. This group is distinguished by dog-faced skulls, with reduced teeth rows, and hypertrophied canines. In this study, we describe a new bauruschid from the Adamantina Formation (Bauru Group), in the southeast Brazil. The new taxon consists of a partial right portion of a skull, and cranial roof elements, fragments of the secondary palate and the lower jaw, as well as, six disarticulated teeth. The new specie is assigned to the Genus Aphaurosuchus due to the presence of a posterior depression on the nasal and the upturned infraorbital jugal ridge. The new species Aphaurosuchus spp. was erected based on characters that distinguish it from Aphaurosuchus escharafacies, such as a large depression on the frontal, a midline longitudinal depression on the frontal, the presence of a crest concealed in the frontal longitudinal depression, and a smooth parietal near the supratemporal fenestrae. To understand the phylogenetic position of Aphaurosuchus spp. among baurusuchids, as well as the taxonomical affinities of newly described and recently revised putative baurusuchians, we performed an updated phylogenetic analysis that combined the information about the baurusuchians from three most up to date and independent matrixes available. We recovered the two main lineage of Baurusuchidae, Pissarrachampsinae and Baurusuchinae as originally proposed. Additionally, we recovered Ogresuchus furatus and Razanandrongobe sakalavae as non-baurusuchids baurusuchians. The novel phylogenetic position for these two taxa increases the spatial distribution and the temporal range of Baurusuchia.
Um novo baurusuquídeo (Crocodiliformes Notosuchia) da Formação Adamantina (Grupo Bauru, Cretáceo Superior), e uma nova análise filogenética dos notosuquios
Keywords: Aphaurusuchus; Baurusuchidae; Baurusuchia; Adamantina Formation; Bauru Basin